Pengaruh Pertumbuhan Penjualan, Profitabilitas, Struktur Modal Dan Likuiditas Terhadap Nilai Perusahaan - Lokassati, Maya Ayu; Hartanti, Rina (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the relationship between Sales Growth, Capital Structure, Profitability and Liquidity on Company Value in mining sector companies listed on the Indonesia Stock Exchange for the period 2020 to 2022. This research uses a purposive sampling technique, with a sample of 16 companies from 63 companies. mining sector for the 2020-2022 period. So the research data used was 48. The analysis techniques used in this research were descriptive statistics, panel data regression, t test (partial), and hypothesis testing. Based on the research results, the variables Sales Growth, Profitability, Capital Structure and Liquidity have no effect and are not significant on Company Value.